MAKNA GANBARU DALAM NOVEL ANATA NO KOE GA KIKITAI KARYA KISHIKAWA ETSUKO - MULYASARI, MAYA (Jurnal Ilmiah Mahasiswa FIB, 2013)
The title of this research is Ganbaru Meaning in the Anata no Koe ga Kikitai Novel written by Estuko Kishikawa. Purpose of the research is to find out ganbaru concept; survive, never give up, and do the best, which are implemented on those two characters, they are Kanako and Mother. By descriptive analysis research methode, there will be attached sixteen datas, and they are divided into two parts, which are eleven datas ganbaru concept of Kanako and five datas ganbaru concept of Mother. This research is expected to show that ganbaru is not always aimed by ourself, but also by others. And finally, most of the ganbaru concept in this research are shown by action, feeling or mind, and sayings. Keywords: Ganbaru, novel, Anata no Koe ga Kikitai, characterizations.